Application of nano bismuth ferrite in friction catalytic degradation of high-concentration methyl orange dye

By friction catalyzing the degradation of high-concentration methyl orange dyes, the problem of difficult degradation of high-concentration dyes in the prior art is solved, and a more efficient catalytic degradation effect is achieved.

CN119771432AActive Publication Date: 2025-04-08LUOYANG NORMAL UNIV

Patent Information

Application Number
CN202411972258.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The existing catalytic degradation methods are difficult to effectively degrade high-concentration methyl orange dyes, and photocatalysis has problems such as low light energy utilization and ultraviolet light dependence.

Method used

Bismuth nanoferrate is used to catalyze the degradation of high-concentration methyl orange dye through friction, and the friction turntable is rotated by external force. The bismuth ferrite nanopowder comes into contact with the methyl orange solution to complete the catalytic degradation.

Benefits of technology

Under the same conditions, bismuth nanoferrate can completely degrade 40mg/L of methyl orange solution by friction catalysis in just 210 minutes, while titanium dioxide nanopowder takes 720 minutes, significantly improving the catalytic degradation efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771432A_ABST
    Figure CN119771432A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of friction catalytic degradation of pollutants, in particular to application of nano bismuth ferrite in friction catalytic degradation of high-concentration methyl orange dyestuff, and a specific catalysis method comprises the following steps: S1, pouring a methyl orange solution into a container, and adding bismuth ferrite nano powder into the methyl orange solution; s2, adding a friction turntable into the container, wherein the bottom surface of the friction turntable is in contact with the bottom surface of the container; s3, enabling the friction turntable to rotate through external force, and completing catalytic degradation of methyl orange by the bismuth ferrite nano powder. According to the method, methyl orange is degraded in a friction catalysis manner, so that the degradation efficiency is greatly improved, and further exploration of a friction catalyst is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of friction catalytic degradation of pollutants, in particular to application of nano bismuth ferrite in friction catalytic degradation of high-concentration methyl orange dye. Background Art

[0002] The international community generally believes that water pollution is a serious problem. The discharge of organic dyes into wastewater from industries such as textiles, leather, food, and chemicals poses a serious threat to the health of water bodies. Organic dyes are widely used as colorants in industries such as textiles, cosmetics, leather, papermaking, plastics, printing, rubber, and medicine, and their use has caused serious water pollution. Dyes affect the human central nervous system, liver, kidneys, skin, enzyme systems, chromosomes, and reproductive systems. Among them, methyl orange (MO) is one of the most widely used harmful anionic azo dyes. Due to its complex aromatic composition and diverse biological properties, it has become a highly persistent and difficult-to-handle xenobiotic, posing a significant burden to humans.

[0003] The existing catalytic degradation methods include adsorption, electrocatalysis, photocatalysis, etc. These technologies have their own advantages and disadvantages. For example, photocatalysis, as a mainstream catalytic method, plays an irreplaceable role in the degradation of toxic substances, dye conversion, energy conversion, etc. However, photocatalysis has low light energy utilization, strong dependence on ultraviolet light, high electron-hole recombination rate, and once the reaction starts, the subsequent reaction is difficult to control. In order to face the increasing environmental crisis, people have turned their research attention to the mechanical energy in the environment.

[0004] It is well known that mechanical energy can be easily absorbed by materials through friction and converted into other forms of energy, including chemical energy, heat energy and light energy. In recent years, the concept of converting mechanical energy into chemical energy through friction, namely tribocatalysis, has attracted more and more attention as an emerging energy collection and conversion method. Bismuth ferrite is a narrow bandgap semiconductor material with a bandgap width of 2.08eV. The energy generated during friction promotes e - and h + The free radical capture experiment showed that h + It is the main active substance in the friction catalytic process and is beneficial to the catalytic decomposition of methyl orange. Summary of the invention

[0005] The purpose of the present invention is to provide an application of nano bismuth ferrite in the friction catalytic degradation of high-concentration methyl orange dye, so as to solve the problems raised in the above background technology.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] Application of nano bismuth ferrite in friction catalytic degradation of high-concentration methyl orange dye.

[0008] Furthermore, the application method comprises the following steps:

[0009] S1, pouring methyl orange solution into a container, and adding bismuth ferrite nanopowder into the methyl orange solution;

[0010] S2, placing the friction disc into the container, with the bottom surface of the friction disc in contact with the bottom surface of the container;

[0011] S3. The friction turntable is rotated by external force, and the bismuth ferrite nanopowder completes the catalytic degradation of methyl orange.

[0012] Furthermore, the concentration of the methyl orange solution is 10-40 mg / L.

[0013] Furthermore, the mass ratio between the bismuth ferrite nanopowder and the methyl orange solution is 1:(900-1100).

[0014] Furthermore, the particle size of the bismuth ferrite nanopowder is 100-200 nm.

[0015] Furthermore, a groove is formed on the bottom surface of the friction rotating disk.

[0016] Furthermore, the rotation speed of the friction disc is 350-500 rpm.

[0017] Furthermore, the temperature at which the bismuth ferrite nanopowder frictionally catalyzes the degradation of methyl orange is 15-30°C.

[0018] Furthermore, the bismuth ferrite nanopowder is prepared by a sol-gel method using ferric nitrate as an iron source and bismuth nitrate as a bismuth source.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The present invention adopts a sol-gel method to prepare bismuth ferrite nanopowder, and uses it to degrade methyl orange by friction. Compared with titanium dioxide nanopowder (P25), the methyl orange dye is catalytically degraded at concentrations of 10 mg / L, 20 mg / L, 30 mg / L and 40 mg / L. The results show that the bismuth ferrite nanopowder (BFO) can completely degrade a methyl orange solution with a concentration of 40 mg / L by friction in only 210 minutes, while TiO2 (P25) requires 720 minutes. The present invention confirms that the multiferroic nanoparticles with a perovskite structure are an economical and environmentally friendly friction catalyst, which promotes further exploration of friction catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is the XRD pattern of BFO in the present invention;

[0022] Figure 2is the SEM image of BFO in the present invention;

[0023] Figure 3 is the SEM image of P25 in the present invention;

[0024] Figure 4 Schematic diagram of the friction catalytic degradation of 40 mg / L methyl orange by BFO in the present invention;

[0025] Figure 5 Schematic diagram of P25 friction catalytic degradation of 40 mg / L methyl orange in the present invention

[0026] Figure 6 It is a curve diagram of the degradation rate of BFO to methyl orange of different concentrations in the present invention;

[0027] Figure 7 It is a curve diagram of the degradation rate of P25 to methyl orange of different concentrations in the present invention;

[0028] Figure 8 Schematic diagram of the degradation of 40 mg / L methyl orange by a single magnetic particle of BFO in the present invention;

[0029] Fig. 9 This is a diagram of the BFO active species capture experiment in the present invention;

[0030] Fig.10 This is a diagram of the friction catalysis mechanism of BFO in the present invention;

[0031] Fig.11 A schematic diagram of a friction rotating disk used in the present invention;

[0032] Fig.12 It is the ultraviolet diffuse reflection graph of BFO and P25 in the present invention;

[0033] Fig.13 This is the band gap diagram of BFO and P25 in the present invention. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] See also Figures 1 to 13 , the present invention provides:

[0036] Application of nano bismuth ferrite in friction catalytic degradation of high concentration methyl orange dye,

[0037] (I) Preparation of bismuth ferrite nanopowder

[0038] The preparation of bismuth ferrite nanopowder adopts the following steps:

[0039] S101, weigh out 20 ml of ethylene glycol solution with a measuring cylinder, and then weigh out 0.02 mol (8.2112 g) of Fe(NO3)3·9H2O, mix the two and pour them into a beaker, and stir them on a magnetic heating stirrer at 50°C for 1.5 hours; then weigh out 60 ml of ethylene glycol solution with a measuring cylinder and weigh out 0.021 mol of Bi(NO3)3·5H2O (10.4853 g, 5% excess is required because bismuth is volatile when heated) with a balance, mix the two and pour them into a beaker, and stir them on a magnetic heating stirrer at 50°C for 1.5 hours to fully dissolve them; finally, mix the solutions in the two beakers, stir them continuously at 60°C for 3 hours in a magnetic heating stirrer until they are fully mixed, and then let them stand for a period of time to form a deep red sol;

[0040] S102, the dark red sol prepared in step S101 is placed in a drying oven set at 100°C to dry for 96 hours. During the drying process, it is found that a thin film begins to appear on the sample after about 4 hours. After 72 hours, all samples are dried and aged into block-like dry gels. Then, the mortar and pestle are cleaned, and the dried samples are placed in them and slowly ground;

[0041] S103, put the powdered sample prepared in S102 into a porcelain boat, mark the excess sample powder and seal it for later use, then put the porcelain boat into a tubular muffle furnace, set the program to heat from room temperature to 120°C for 30 minutes and keep it for 40 minutes, then heat to 300°C for 30 minutes and keep it for 40 minutes, then heat to 600°C for 30 minutes and keep it for 3 hours, finally end the heating, wait for it to cool naturally, and the color of the sample turns into khaki after annealing;

[0042] S104, the khaki powder obtained in step S103 is washed with 10% dilute nitric acid, and then washed again with deionized water, and dried in a drying oven at 100° C. for about three hours to obtain the desired bismuth ferrite nanopowder.

[0043] (II) Analysis of samples and characterization tests

[0044] The XRD spectra of the samples used in the experiment are shown in Figure 1As shown in the figure, the card number (XRD standard card library number) of bismuth ferrite nanopowder (BFO) prepared by sol-gel method is highly consistent with the perovskite structure, indicating that sol-gel method is a better method for preparing single-phase BFO nanopowder; the titanium dioxide nanopowder (P25) used in this experiment is commercially available P25; XRD results show that P25 is anatase phase (PD#21-1272) TiO2 and rutile phase (PDF#21-2176) TiO2, which is consistent with the known composition and structure of P25; the electron microscope images of the two materials are shown in Figure 2 (BFO) and Figure 3 As shown in (P25), the particle size of P25 is about 50nm, and the particle size of BFO is distributed between 100-200nm.

[0045] (III) Experiment on friction catalytic degradation of methyl orange

[0046] 0.3 g of BFO nanopowder and P25 nanopowder were added into 30 mL of methyl orange solution (10 mg / L, 20 mg / L, 30 mg / L, 40 mg / L), respectively. The degradation rate curves of BFO nanopowder and P25 nanopowder for different concentrations of methyl orange were as shown below: Figure 6 and Figure 7 As shown, the methyl orange solution is contained in a glass beaker (420 mm × 600 mm), and a Teflon turntable (a cross-groove friction turntable specially designed by Li et al. for monitoring degradation details) is placed in the suspension. The turntable contacts the bottom of the glass beaker to generate friction mechanical energy. The turntable structure is as shown in FIG. Fig.11 As shown), the beaker was sealed and placed in the dark at 20°C and magnetically stirred at 400 rpm; 3 ml of the suspension was sampled at fixed intervals to characterize the fading; the suspension was immediately centrifuged after collection and tested by UV-visible spectrophotometer; the results were shown in Figure 4 , Figure 5 It can be found (for the catalytic degradation experiment of 40 mg / L methyl orange solution) that compared with P25 nanopowder, the BFO nanopowder prepared by the sol-gel method exhibits excellent friction catalytic degradation performance for the difficult-to-degrade methyl orange organic dye.

[0047] (IV) Comparative experiment to verify that the degradation of methyl orange is not due to adsorption of nanomaterials

[0048] In order to prove the friction catalytic effect of BFO nanopowder, a BFO single magnetic particle degradation experiment was carried out (in this experiment, the single magnetic particle did not contact the bottom of the glass beaker and did not generate friction mechanical energy) to clarify that physical adsorption does not play a major role in the degradation process of methyl orange dye; by using magnetic particles with rubber washers to stir, the friction catalytic effect was eliminated, and after regular sampling, UV-visible spectrophotometer tests were performed; the results are shown in Figure 2. Figure 8As shown in the figure, the peak position of methyl orange also decreases with the passage of time, but the degradation time is much longer than that of friction catalysis. When degrading 40 mg / L methyl orange dye, the peak position is still very high after 8 hours, and the adsorption amount is only 40%. Using the friction catalytic turntable, the high concentration of 40 mg / L methyl orange dye is almost completely degraded within 210 minutes, which fully demonstrates the excellent performance of friction catalysis and proves that the degradation of methyl orange can be efficiently completed through friction catalysis by BFO nanopowder.

[0049] (V) Experiment on active species capture of bismuth ferrite nanopowder

[0050] Before the experiment, 0.03mmol BQ, 0.03mmol EDTA-2Na, 0.03mmol TBA and 0.03mmol AgNO3 were introduced into a beaker containing 300mg BFO nanoparticles and 30mL methyl orange solution with a concentration of 40mg / L. These scavengers can effectively neutralize ·O 2- Free radicals, h + , OH radicals and e - Subsequently, the same conditions as those for the methyl orange dye degradation experiment were used to evaluate the catalytic effect of friction on dye degradation. The results are shown in Fig. 9 As shown, from Fig. 9 It can be seen that the active substance of BFO tribocatalytic degradation of methyl orange is h + At the same time, the active role of oxygen ions cannot be ignored. The experimental study on the capture of active substances by P25 showed that both holes and hydroxide ions play a role in the friction-catalyzed degradation of methyl orange dye. Based on this, the following conclusions were drawn: Fig.10 The diagram shows the friction catalytic mechanism of BFO nanopowder.

[0051] Compared with various catalytic materials, bismuth ferrite materials have a narrow band gap structure such as Figure 12-13 ( Fig.12 The UV diffuse reflectance images of BFO and P25 are shown below. Fig.13 (Band gap diagram of BFO and P25) It can quickly degrade high concentration of methyl orange dye under friction catalytic conditions. Compared with P25 nanopowder, at concentrations of 10mg / L, 20mg / L, 30mg / L and 40mg / L, the speed at which BFO nanopowder completely degrades methyl orange dye is 7.5 times, 9.6 times, 3.375 times and 3.429 times that of P25 nanopowder, respectively. It is a high-performance catalyst for degrading methyl orange.

[0052] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. Application of nano bismuth ferrite in friction catalytic degradation of high concentration methyl orange dye.

2. The use of nano bismuth ferrite according to claim 1 in friction catalytic degradation of high concentration methyl orange dye, characterized in that: The application method includes the following steps: S1. Pour the methyl orange solution into a container, and add bismuth ferrite nanopowder into the methyl orange solution; S2, placing the friction disc into the container, with the bottom surface of the friction disc in contact with the bottom surface of the container; S3. The friction turntable is rotated by external force, and the bismuth ferrite nanopowder completes the catalytic degradation of methyl orange.

3. The use of nano bismuth ferrite in friction catalytic degradation of high-concentration methyl orange dye according to claim 1, characterized in that: The concentration of the methyl orange solution is 10-40 mg / L.

4. The use of nano bismuth ferrite in friction catalytic degradation of high-concentration methyl orange dye according to claim 1, characterized in that: The mass ratio between the bismuth ferrite nanopowder and the methyl orange solution is 1:(900-1100).

5. The use of nano bismuth ferrite in friction catalytic degradation of high concentration methyl orange dye according to claim 1, characterized in that: The particle size of the bismuth ferrite nanopowder is 100-200nm.

6. The use of nano bismuth ferrite in friction catalytic degradation of high concentration methyl orange dye according to claim 1, characterized in that: The bottom surface of the friction rotating disk is provided with grooves.

7. The use of nano bismuth ferrite in friction catalytic degradation of high concentration methyl orange dye according to claim 1, characterized in that: The rotation speed of the friction plate is 350-500 rpm.

8. The use of nano bismuth ferrite in friction catalytic degradation of high concentration methyl orange dye according to claim 1, characterized in that: The temperature for friction catalytic degradation of methyl orange by the bismuth ferrite nanopowder is 15-30°C.

9. The use of nano bismuth ferrite in friction catalytic degradation of high concentration methyl orange dye according to claim 1, characterized in that: The bismuth ferrite nanopowder is prepared by using ferric nitrate as an iron source and bismuth nitrate as a bismuth source through a sol-gel method.

Citation Information

Patent Citations

  • Pollutant treatment method based on friction catalysis of semiconductor powder

    CN109850983A

  • Multifunctional multiferroic ceramic polymer composite material and application

    CN111690220A

  • Preparation and piezoelectric-photocatalytic application of oxygen vacancy-containing bismuth ferrite nano material

    CN119098182A

  • Triboelectric energy generating device including ferroelectric composite and driven by ultrasonic wave

    US20230093932A1

Cited By

  • Method for degrading organic pollutants in sewage through friction catalysis and application of method

    CN120364836A

  • Method for degrading pollutants by friction catalytic activation of persulfate

    CN120681869A